Analysis of in-plane wave propagation in periodic structures with Sierpinski-carpet unit cells. (12th May 2017) - Huang, Jiankun; Ruzzene, Massimo; Chen, Shengbing
Abstract: In this study, the dispersion relationships and characteristics of directional periodic structure waveguides with Sierpinski carpet unit cells were investigated. Finite element method was used to analyze the Sierpinski-carpet periodic structures with square Pb cylinders inserted in the rubber background. The dispersion curves of unit cells with different stages were investigated first, then group velocities of periodic structures at given frequencies were calculated and used to analyze the directional waveguide characteristics in the Sierpinski-carpet periodic structures. The dynamic responses of finite periodic structures were investigated to observe the directional features, and the results were used to support the fact that Sierpinski carpet unit cells with different stages can control the propagation behavior of elastic waves in specific ways; the dispersion curves grew compressed as the stage increased. Multiple band characteristics were observed in the case of the second-stage fractal configuration. The directional propagation characteristics in Sierpinski carpet periodic structures can be utilized to further extend the range of vibration reduction zones. The results of this study have significant potential in terms of the application of Sierpinski-carpet periodic structures for vibration isolation.